Adult Neurogenesis in Neurodegenerative Diseases: Figure 1. - Beate Winner; Jürgen Winkler (2015)
Beate Winner1 and Jürgen Winkler2 1IZKF Junior Research Group III, Interdisciplinary Center for Clinical Research, Nikolaus-Fiebiger Center for Molecular Medicine, FAU Erlangen-Nürnberg, 91054 Erlangen, Germany 2Department of Molecular Neurology, FAU Erlangen-Nürnberg, 91054 Erlangen, Germany Correspondence: beate.winneratmed.uni-erlangen.de; juergen.winkleratuk-erlangen.de